2015
DOI: 10.1007/s10641-015-0418-0
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the contributions of ocean ranching and net-pen aquaculture in the successful establishment of Chinook salmon in a Patagonian basin

Abstract: The presence of Chinook salmon in Patagonia is an example of a successful invasion by a Pacific salmon species. The combination of historical records and genetic data can help to determine the origin of invasive / introduced species and allow the identification of the sources and dispersal process. We analyzed the genetic structure of Chinook salmon in the Futaleufú River (Pacific slope basin of Patagonia) using single nucleotide polymorphism genotypes and a recently described baseline dataset of native North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 36 publications
8
33
0
Order By: Relevance
“…These genetic stocks correspond to a large extent to specific source populations that have been identified in a previous study with very dense representation of source collections (146 native populations from 46 genetic lineages; Correa & Moran, ). The other three collections of Chinook Salmon from North America allowed us to account for patterns of natural genomic variation as well as scenarios of colonization from multiple sources or possible admixture (Correa & Gross, ; Di Prinzio et al., ). Despite the first introduction attempts in the early 1900's, stocking history and genetic analyses indicate that current populations of Chinook Salmon originated from introductions in Chile for ocean ranching in the late 1970s and early 1980s primarily from the lower Columbia River (Cowlitz River Hatchery spring‐run; Correa & Gross, ; Di Prinzio et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These genetic stocks correspond to a large extent to specific source populations that have been identified in a previous study with very dense representation of source collections (146 native populations from 46 genetic lineages; Correa & Moran, ). The other three collections of Chinook Salmon from North America allowed us to account for patterns of natural genomic variation as well as scenarios of colonization from multiple sources or possible admixture (Correa & Gross, ; Di Prinzio et al., ). Despite the first introduction attempts in the early 1900's, stocking history and genetic analyses indicate that current populations of Chinook Salmon originated from introductions in Chile for ocean ranching in the late 1970s and early 1980s primarily from the lower Columbia River (Cowlitz River Hatchery spring‐run; Correa & Gross, ; Di Prinzio et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The other three collections of Chinook Salmon from North America allowed us to account for patterns of natural genomic variation as well as scenarios of colonization from multiple sources or possible admixture (Correa & Gross, ; Di Prinzio et al., ). Despite the first introduction attempts in the early 1900's, stocking history and genetic analyses indicate that current populations of Chinook Salmon originated from introductions in Chile for ocean ranching in the late 1970s and early 1980s primarily from the lower Columbia River (Cowlitz River Hatchery spring‐run; Correa & Gross, ; Di Prinzio et al., ). In fact, this lineage prevails in our samples south of 43°S (i.e., Aysén and Baker; Correa & Moran, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past and recent genetics and genomics studies have identified multiple donor populations of Chinook salmon that likely interbred and now coexist among Pacific Ocean and Atlantic Ocean basins (Correa & Moran, ; Narum et al., ; Riva‐Rossi et al., ). Both individual assignment and genetic analysis of population mixtures (McKinney, Seeb, & Seeb, ) have greatly assisted tracking the geographic origin of donor Chinook salmon populations to various sites in South America (Ciancio et al., ; Correa & Moran, ; Di Prinzio et al., ). However, we lack a clear understanding on how genetic diversity, dispersal, and genetic admixture are linked to artificial and natural dispersal pathways of this species from its distributional range in South America.…”
Section: Introductionmentioning
confidence: 99%